TRADITIONAL POSTPARTUM CARE PRACTICES IN SEVERAL ASIAN COUNTRIES: A SYSTEMATIC REVIEW - Nurdiana Lante, Muh. Syafar, Syamsuar Manyullei, Yahya Thamrin, Shanty rizkiyani, Andi Nilawati (Chelonian Research Foundation, 2024)
Background: Traditional postpartum care practices in several Asian countries have become an important part of local culture and heritage but have not been studied systematically. Objective: This study aimed to restructure the existing information regarding traditional postpartum care practices in Asian countries to provide a more comprehensive understanding. Methods: A systematic review involved five stages: identifying the research question, identifying relevant studies, selecting studies, charting data, collating, summarizing, and reporting results. To identify relevant studies, a systematic search was conducted using the PubMed, SCOPUS, Google Scholar, and Proquest databases for articles published between 2013 and 2023. Data from the included studies were charted using a standardized data extraction form. The form includes information on the Subject, Country, Findings. Results: The findings show that traditional postpartum care practices in West and East Asia include avoiding certain foods, limiting activities to bed rest in South Asia and Central Asia, and that postpartum mothers apply unsafe practices based on cultural beliefs because of the costs and lack of awareness. In Southeast Asia, in general, they adhere to the traditional understanding of health and disease in the postpartum period, which is centered on warming the body, steaming through diet, and other heat applications, which are understood as ways of preventing postpartum disease. They carried out this practice to respect traditions and follow the advice of their parents. Conclusion: The postpartum care practices of Asian countries vary regionally, posing potential risks. Improving standards and collaboration, focusing on women's education and local maternal–child health service providers, is crucial for improving maternal health.